Chapter Transizioni per il lavoro in Higher Education: il ruolo del Dottorato di Ricerca in Italia - Boffo, Vanna (Studies on Adult Learning and Education, 2022)
The transformations of the figures of the professional family of educational research and, as a consequence, of doctoral paths of the last decade, open up to multiple possibilities and to as many tasks for those who deal with planning in Higher Education. The identification of the underlying patterns of the training paths can contribute to responding fully to these challenges. Above all, the pedagogical principle of employability, with its integral and transformative value, can become an effective design operator of Higher Education in general, and of PhD courses in particular.